EVOLUTIONARY BIFURCATION CONCEPT THE DEVELOPMENT OF ECONOMIC SCIENCE - O. V. Karamova (Модернизация, инновация, развитие, 2016)
New subject-object approach to periodization of economics used in science philosophy is substantiated. Three science development periods (classical, nonclassical and postnonclassical) are characterized. Author’s concept of evolutionary-bifurcational development of economics as a science is substantiated.